PENGUKURAN PENGGUNAAN LAHAN CAMPURAN (MIXED USE) DENGAN INDEKS ENTROPY DI KOTA SEMARANG - Artha Segnita; Wiwandari Handayani (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
Mixed use development is one of the supporting aspects of compact city in sustainable urban development that focuses on developing areas with various functions such as residential, commercial, office, and other supporting facilities developed and built in one area. This concept addresses the need of availability optimization in a limited land area. This paper aims to study the mixed use in supporting the compact and sustainable space in Semarang City, as planned in “RTRW Kota Semarang 2011-2031”. For this purpose, mixed use cities can be measured from land use patterns and mixed land use rates. The Entropy Index is a measure of the level of mixed use that takes into account the relative percentage of two or more land use types in a region. The size of the entropy index indicates that good land use in a given area is relatively balanced against other land uses within certain area boundaries. The existing land use distribution for each region is obtained from shapefile of urban land use and image interpretation. Therefore, this study uses quantitative measures of spatial mixed use through the use of Geographic Information System (GIS) data. Finally, we find that in the city center there are areas that are considered as an example of the development of mixed use in Semarang City, which is located in Central Semarang subdistrict (Pekunden, Karangkidul, Brumbungan, and Jagalan).